Global financial crisis and trade slowdown in Sub-Sahara Africa: panel VAR analysis for growth and poverty outcomes. (1st January 2012) - Ajilore, Taiwo; Ikhide, Sylvanus
The global financial crisis hit the economies of most commodities exporting countries of Sub-Sahara Africa (SSA) mainly through trade and commodities prices collapse. Theoretical and empirical literature postulates debilitating effects of these on growth, poverty and sustainable development outcomes. This study utilised aggregate data on selected SSA countries and panel vector autoregressions method to obtain an empirical gauge of these effects. This study documents a positive influence of trade on growth rates, while both trade and growth indicate potentials for poverty reduction in SSA. These findings raise important policy concerns for sustainable development, growth and poverty outcomes in SSA countries. For policy, this study recommends efforts directed at a pro-poor trade expansionist policies, diversification of the export base and spending programmes that create jobs, ensure the delivery of core services and provide safety nets at country levels, while at global level, efforts to support trade finance in developing countries, including SSA should be invigorated.